2009
DOI: 10.1016/j.vetmic.2008.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the laboratory diagnosis of chlamydial infections

Abstract: A., Longbottom, D., Recent developments in the laboratory diagnosis of chlamydial infections, Veterinary Microbiology (2008Microbiology ( ), doi:10.1016Microbiology ( /j.vetmic.2008 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
113
0
27

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(148 citation statements)
references
References 147 publications
2
113
0
27
Order By: Relevance
“…Isolation of the pathogen and specialized culture techniques was once the "gold standard" method. Today it is considered that maintenance of bacteria viability in the specimen is a limit to effectiveness (Sachse et al 2009, Sykes 2005. Isolation is also time consuming, therefore routine diagnosis is dominated by methods which quickly provide a test result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of the pathogen and specialized culture techniques was once the "gold standard" method. Today it is considered that maintenance of bacteria viability in the specimen is a limit to effectiveness (Sachse et al 2009, Sykes 2005. Isolation is also time consuming, therefore routine diagnosis is dominated by methods which quickly provide a test result.…”
Section: Discussionmentioning
confidence: 99%
“…Commercially available tests such as an immunoenzymatic assay (ELISA) or immunofluorescence assay (IFA) are based on family-specific lipopolisaccharide (LPS) antigens. The monoclonal antibodies used in the IFA are directed against a genus-specific epitope located on the chlamydial LPS (Ohya et al 2008, Sachse et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…5 Chlamydial infections can be detected either by isolation of pathogens or by screening for antibodies in tissue scrapings and smears, tissue sections, serum, and bodily secretions. 27,29 Because of the insufficient sensitivity, low specificity, and low pathogen loads of clinical samples, it is difficult to detect infection status by means of such tests. 29 Alternative methodologies based on nucleic acid amplification, such as polymerase chain reaction (PCR), which possess both unsurpassed sensitivity and specificity, have been recently used to diagnose human chlamydiosis.…”
Section: Introductionmentioning
confidence: 99%
“…These species cause host-specific infections in humans and different animal species. Some strains are adapted to animals and have zoonotic potential (Everett et al 1999;Sachse et al 2009). C. abortus is responsible for ovine enzootic abortion (OEA) in sheep and goats (Longbottom and Coulter 2003), but is less common in cattle (Borel et al 2006).…”
mentioning
confidence: 99%
“…Due to the low sensitivity of this technique, however, the method has now been superseded by ELISA (Aitken and Longbottom 2004). PCR has been used widely in the diagnosis of infectious agents at the level of genus, species and strain (Sachse et al 2009). It was shown that pmp gene-specific primers have a higher sensitivity and specificity for detecting C. abortus (Laroucau et al 2001;Greco et al 2005).…”
mentioning
confidence: 99%